PENGARUH HARGA KARPET, PENDAPATAN KONSUMEN DAN USIA TERHADAP PERMINTAAN KARPET DI PASAR SUDIMAMPIR KOTA BANJARMASIN - MUHAMMAD RIFANI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research was conducted to know (1) what is the price of carpet, consumer income and age take effect simultaneously to a request of the carpet Market in Sudimampir town of Banjarmasin; (2) where the most dominant Factor effect partially to a request of the carpet Market in Sudimampir town of Banjarmasin.Respondents who were sampled in the processing of the data amounted to 41 people. Data processed by using multiple linear analysis to see the influence of the independent variable (the price of carpet, consumer income and age) of the dependent variable (the demand for carpet).Multiple linear regression results this research proves a significant relationship between the price of carpets and carpet requests against consumer income in the market Sudimampir the city of Banjarmasin.This relationship indicates that the higher the price of the carpet then request the carpet will go down, otherwise when the price is low then the carpet carpet demand is going up.In addition, the greater the income consumers then request the carpet will be increased, on the contrary when consumer income is small then the carpet request will be declined.As for the age to do not significantly to request the carpet on the market Sudimampir the city of Banjarmasin.Keywords: Demand For Carpets, Carpet Prices, Consumer Income, Age